Transactional Analysis: Measuring "Ego States" - Maheshwari, Nidhi; Bijawat, Swati; Tandon, Neha (Prabandhan: Indian Journal of Management, 2009)
Transactional Analysis (TA) is one of the most accessible theories of modern psychology. It highlights three ego states: Parent, adult and child (PAC) of every person. The objective of this paper is to analyze the different ego states of retail professionals in Jaipur city and thereby determines the "dominant ego" with the help of an "Egogram" a tool developed by Dusay in (1977) and a validated questionnaire used in the research paper "Transactional analysis: Measuring Ego States" written by "Jose T Payyappily, N. Rajagopal Anitha Zachariah". The questionnaire is developed by ICTA (the institute of counseling and transactional analysis), Kerala for measuring the six ego statuses of the people. The another objective is to help retail professional to understand and adapt their behavior and develop more effective ways of communicating.